Analisis Sumber Daya Manusia, Sistem Informasi Akuntansi dan Sistem Pengendalian Internal dalam Optimalisasi Penerapan PSAK No.109 di BAZNAS Provinsi Jawa Barat - Taupik Taupik; Jalaluddin Jalaluddin (Ma'soem University, 2022)
The background in optimizing the application of PSAK No.109 is still often found inaccuracy of Acoounting Staff in making financial statements and the unavailability of an automatic financial statement recording system in making financial statements.This study aims to find out how the analysis of human resources, accounting information systems and internal control systems in optimizing the application of PSAK No.109 in the Amil Zakat Agency of West Java Province.This research is a qualitative research with a descriptive approach. The data used is primary data, with information taken on amyl and financial statements of BAZNAS of West Java Province. The data collection techniques carried out are observation, interviews, literature studies and documentation. The results showed that the head of the Department of Human Resources, Administration and General, Accounting Staff and Chairman of the Internal Audit Unit has applied aspects of human resources, accounting information systems and internal control systems in conducting analysis on the optimization of the application of PSAK No.109. Aspects that play a role in optimizing the application of PSAK No.109 are SDM, SPI and SIA. Assessment of HR aspects amounted to 3 points. The assessment of the SIA aspect amounted to 4 points. The assessment of the SPI aspect amounted to 9 points. If the analysis of human resources, SIA and SPI has been applied, there are 9 stages to apply PSAK No.109 which must be done in order seseuai with the provisions contained in PSAK No.109.